Microplastic Detection in Soil Amended With Municipal Solid Waste Composts as Revealed by Transmission Electronic Microscopy and Pyrolysis/GC/MS - Watteau, Francoise; Dignac, Marie-France; Bouchard, Adeline; Revallier, Agathe; Houot, Sabine (Frontiers in Sustainable Food Systems, 2018)
Urban compost application in agroecosystems enhances soil fertility but can also be a source of (micro) plastics, which are not completely removed during the composting process. Knowledge of the fate of these plastics in regularly-amended soils is thus an issue for the environmental management of these soils. The aims of this study were (1) to develop a method combining soil fractionation, microscopic observation and chemical characterization to follow the fate of plastics in soils and (2) to apply this method on a long-term experimental field, where municipal solid waste composts were applied every other year during 10 years. The presence of plastics was investigated within compost and soil fractions using morphological and analytical characterization by transmission electronic microscopy (TEM-EDX) and pyrolysis coupled to gas chromatography and mass spectrometry (Py/GC/MS). Specific features of plastics allowed us to distinguish these polymers from soil organic matter even in the <200 μm soil fractions. Ti and Ba detection associated with these features, as they are initially added during the polymer production, also constituted plastic tracers within organo-mineral fractions. Plastic fragments as detected by TEM were less abundant in the fine soil fractions compared to the coarsest ones. The abundance of styrene produced upon pyrolysis, used as a molecular tracer of plastics, also decreased relative to produced toluene according to the same particle size gradient. Our results evidenced that plastics and microplastics were present in the soil that was amended for 10 years with compost, while not in the control soil. MPs were mostly observed as individualized particles, present in the coarsest fractions as well as some of the fine soil fractions, but they were little associated with the soil matrix. They mostly did not show any degradation features such as microbial lysis. We thus suggest that their evolution in soil was mainly due to fragmentation. Our methodological approach provides tools to monitor the fate of microplastics over time and specify the contribution of such contaminants in soil amended with bio-based products.